AKTIVITAS PENANGKAPAN RADIKAL BEBAS DAN POTENSI ANTIHIPERGLIKEMIK BEBERAPA GAMBIR DARI BEBERAPA PASAR INDONESIA - GALUH WIDIYARTI; ANDINI SUNDOWO (Fakultas Farmasi Universitas Pancasila, 2012)
Gambier (uncaria gambier) is known to have antioxidant properties and some studies attributed to the presence of polyphenols. The objective of this study was to investigate the potential of various gambier available in Indonesian market as free radical scavenger and to evaluate its antihyperglycemic potency as α-glucosidase inhibator. Isolation of catechin was carried out by extraction with distilled ethyl acetate as solvent. Analysis of catechin in the gambier dried extracts were carried out by TLC method. The molecular weight and catechin content of gambier dried extracts were determined by analyzing mass spectra and spectrophotometry, respectively. The free radical scavenging aactivity ofextracts were measured by using 1, 1-diphenyl1-2-picrylhydrazyl (DPPH) as stable free radical compound. The antihyperglycemic potency of gambier dried extracts were asseyed, as α-glucosidase inhibator. The results showed that various gambier available in the market were very active as antioxidant, indicated by the IC50 vvalues of gambier dried extracts were 4.6 to 18.2 µg/mL. Whilst th IC50 for glucosidase inhibition varies from 40.45 to 52.43 µg/mL, and classified as a moderate antidiabetic.